1985
DOI: 10.1177/153944928500500303
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Leadership and Staff OTR Job Satisfaction

Abstract: The primary objective of this investigation was to explore the effects ofthe managerial leadership ofhospital-based occupational therapy directors on their registered occupational therapy (OTR) staffmembers' job satisfaction. Leadership behaviors, power and influence factors, skills, and overall managerial leadership effectiveness were tested for their correlation with staffjob satisfaction. In order to test the conceptualizations, mailed questionnaires were completed by 93 occupational therapy department dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…Direct service respondents also rated organizational supportfor training (Christiansen, 1970) as a disincentive. These work incentives and disincentives for occupational therapists are consistent with those reported by Brollier (1985a).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Direct service respondents also rated organizational supportfor training (Christiansen, 1970) as a disincentive. These work incentives and disincentives for occupational therapists are consistent with those reported by Brollier (1985a).…”
Section: Discussionsupporting
confidence: 87%
“…They concluded that this imbalance may be linked to job dissatisfaction and burnout in occupational therapists. Brollier (1985a) examined the relationship between staff occupational therapists' job satisfaction and their supervisor's leadership style. She found that supervisory style significantly influenced staffsatisfaction, although supervisors were largely unaware of their impact.…”
mentioning
confidence: 99%
“…Respondents reported the most favourable ratings on those job satisfaction factors that reflected general satisfaction with work and communication and co-operation among team members. This is in accordance with Brollier (8), who found that non-managerial occupational therapists were most satisfied with their co-workers and with occupational therapy as a kind of work. The respondents in the present study were also fairly satisfied with the managerial feedback.…”
Section: Job Satisfaction Social Support and Supervisionsupporting
confidence: 91%
“…164). Negotiation skills are also necessary for occupational therapists to be able to maintain existing departments and to use influence to further departmental growth and staff development to provide the best possible services to clients (Brollier, 1985). Training in assertiveness may also assist occupational therapists to return to the work force after a break (Turner, 1992).…”
Section: Power Dynamics and The Occupational Therapistmentioning
confidence: 99%